Análisis multiestado multivariado de la formación y disolución de las parejas conyugales en México - Pérez Amador, Julieta (El Colegio de México A.C., 2008)
This article analyzes the formation and dissolution of conjugal couples in Mexico. Information from Enadid 1997 is used to model the process using the analysis of the history of events based on a scheme that simultaneously considers five states and seven transitions, which makes it possible to estimate both the risk of transition between states and the effect of variables associated with the occurrence of transitions. The results suggest that although women of recent generations are postponing marriage, they are also entering common-law marriage at an earlier age. The likelihood of legalizing common-law marriages is higher than the risk of dissolution. Nevertheless, the common-law marriages entered into by women of recent generations are more likely to dissolve in comparison with those of women of previous generations. Likewise, the dissolution of legal union is greater in younger generations. Although factors associated with separation or divorce are similar for both types of union, common law marriages are more likely to dissolve than marriages. These results contribute to the debate that attempts to place Mexico within the “second demographic transition”.